The friars in Ireland, 1224-1540 - Ó Clabaigh, Colmán N. (Four Courts Press, 2012)
"This work surveys the history, lifestyle and impact of the friars in Ireland from the arrival of the Dominicans in 1224 to the Henrican campaign to dissolve the religious houses in 1540. It constitutes the first attempt to examine the mendicant phenomenon as a whole rather than focusing on individual orders and friaries. The first three chapters give a chronological overview of the arrival and initial expansion of the friars in the thirteenth century, through the upheavals of the fourteenth century and the emergence of vigorous reform parties within each order in the fifteenth and early sixteenth centuries. The second section consists of seven chapters that examine discrete aspects of mendicant lifestyle and ministry. These include analyses of the friars' relationships with their patrons, benefactors and critics. The mendicant lifestyle forms the subject of one chapter, as does the friars' efficacy as preachers, confessors and counsellors. Particular attention is devoted to the educational and formation structures within each order, as well as to devotional and liturgical activities. The art and architecture of the friaries is examined in another chapter. The volume concludes with an epilogue detailing the developments and upheavals in Irish mendicant life during the tumultuous decade between 1530 and 1540"--Page 4 of cover